Sosialisasi Pemanfaatan Aplikasi Digital Platform Livin' by Mandiri pada Masyarakat Penerima Bantuan Sosial - Setiawan, Topan (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2023)
This socialization activity was carried out in order to provide knowledge to the public or customers who are also recipients of social assistance regarding the use of the Livin' by Mandiri digital platform application. The goal is for customers to have easy access to banking services anytime and anywhere, as well as to encourage and strengthen the shift in the use of banking services from conventional to digital technology. The methods used in this activity are lecture and educational methods. The results of this activity have had a good impact where customers have enthusiasm and interest in utilizing digital services in the future. That way the knowledge and utilization of banking digitalization in people in remote areas will increase.